2015
DOI: 10.1161/jaha.115.002309
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Correlates of Abnormal Aortic Root Dimension in an Adult Population: The Strong Heart Study

Abstract: BackgroundWe evaluated the relationship of aortic root dimension (ARD) with flow output and both peripheral and central blood pressure, using multivariable equations predicting ideal sex‐specific ARD at a given age and body height.Methods and ResultsWe measured echocardiographic diastolic ARD at the sinuses of Valsalva in 3160 adults (aged 42±16 years, 61% women) from the fourth examination of the Strong Heart Study who were free of prevalent coronary heart disease, and we compared measured data with the theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
(86 reference statements)
4
12
0
Order By: Relevance
“…Consistent with our results, small ARD, as raw, unindexed measure at the level of Valsalva sinuses, has been associated with prevalent hypertension and suggested to be an important etiological factor in development of systolic hypertension [8,11,12]. Also cross-sectional analyses from the Framingham Heart Study reported that ARD was positively associated with both mean and DBP, whereas it was negatively associated with PP and SBP [9], both indirect markers of increased arterial stiffness.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with our results, small ARD, as raw, unindexed measure at the level of Valsalva sinuses, has been associated with prevalent hypertension and suggested to be an important etiological factor in development of systolic hypertension [8,11,12]. Also cross-sectional analyses from the Framingham Heart Study reported that ARD was positively associated with both mean and DBP, whereas it was negatively associated with PP and SBP [9], both indirect markers of increased arterial stiffness.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, different methods of measuring ARD potentially impose a major bias in the evaluation, because the arterial remodeling in aging and hypertension tends to increase leading edge-to-leading edge diameter, while reducing the trailing edge-to-trailing edge diameter, making results from metaanalyses that mixes studies using both these measure of ARD confusing and difficult to interpret [29]. Most recently, we demonstrated in the cohort of the Strong Heart Study, that age, sex and body size-independent aortic dilatation evaluated as in the present analysis, strongly depends on the extend of hemodynamic determinant, including BP components and LV performance [12].…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations